A qualitative analysis of STEM female’s coping strategy under the COVID-19 pandemic - Tien, Hsiu-Lan Shelley; Gong, Lei; Wang, Wei-Hsuan; Lee, James (Frontiers in Public Health, 2023)
The purpose of the research was to realize the STEM female’s career coping under the pandemic. We conducted in-depth interviews with three STEM female engineers in Silicon Valley, California. After analyzing the research results, we found that: (1) In response to the impact of the pandemic, technology companies and female workers have demonstrated their ability to respond quickly; (2) While working from home, STEM females experienced five notable challenges, but also developed corresponding coping strategies; (3) Corporate systems and teamwork in the STEM fields utilize external resources to help female workers respond effectively to the pandemic.